A la découverte de la biodiversite, de l’environnement et des perspectives des populations locales dans les paysages forestiers: methodes pour une etude pluridisciplinaire du paysage - Sheil, Douglas; Puri, R.K.; Basuki, I.; Heist, M. van; Wan, M.; Liswanti, N.; Rukmiyati; Sardjono, M.A.; Samsoedin, I.; Sidiyasa, K.D.; Chrisandini; Permana, E.; et al. (Center for International Forestry Research, 2004)
This book for the first time brings together a suite of effective methods as a guidance on how to deal with the needs of local communities and biodiversity in landscapes required by decision makers. The techniques provide conventional biophysical descriptions of the landscape and explicitly relate this information to local needs, preferences and value systems. These methods can be used to guide future research and to make recommendations on options about land use and policy. The methods described in this report also provide a foundation for deeper dialogue with the forest communities.